Evaluation of player-surface interaction on artificial soccer turf during cutting movements - Müller, C.; Sterzing, T.; Lange, J.; Milani, T. L. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to evaluate the traction characteristics of four different stud configurations on 2-Star, third generation artificial soccer turf during cutting movements. Traction, among others, characterizes player-surface interaction and is a key for top level performance in soccer. The concept of this study involves a combination of performance, subjective-sensory and biomechanical testing. Parameters of this study were: running times, subjective rankings and ratings and ground reaction forces. A subject pool of 26 soccer players was available for the study. The results show that subjects run slower, perceive worse, and evoke lower shear force values in soft ground design (p<0.01). It is concluded that a hard ground or partly a firm ground stud configuration is better suited than a soft ground stud configuration for playing on artificial turf. In this study, number, geometry and positioning of studs were the important aspects to achieve good and functional traction. With regard to methodological considerations, the combined approach consisting of three interdependent studies shows valuable and necessary insight of traction properties of different shoe-surface interfaces.